2020
DOI: 10.3390/pathogens9020140
|View full text |Cite
|
Sign up to set email alerts
|

The Diverse Functions of the Ubiquitous Fcγ Receptors and Their Unique Constituent, FcRγ Subunit

Abstract: Fc gamma receptors (FcγRs) are widely expressed on a variety of immune cells and play a myriad of regulatory roles in the immune system because of their structural diversity. Apart from their indispensable role in specific binding to the Fc portion of antibody subsets, FcγRs manifest diverse biological functions upon binding to their putative ligands. Examples of such manifestation include phagocytosis, presentation of antigens, mediation of antibody-dependent cellular cytotoxicity, anaphylactic reactions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 84 publications
(104 reference statements)
1
13
0
Order By: Relevance
“…The decreased immunoregulatory function of adaptive CD56 dim NK cells may result from the low NCR expression. This is in line with previous reports in the LCMV mouse system [55][56][57], showing, for example, that an altered regulation of CD8 + T cells by NK cells in FcεRIγ -/mice resulted in better survival. However, it remains unclear whether the FcεRIγ -/-NK cells in this mouse model are comparable to their human counterparts since, in the murine system, adaptive/memory-like NK cells are defined by other features such as Ly49H expression.…”
Section: Discussionsupporting
confidence: 93%
“…The decreased immunoregulatory function of adaptive CD56 dim NK cells may result from the low NCR expression. This is in line with previous reports in the LCMV mouse system [55][56][57], showing, for example, that an altered regulation of CD8 + T cells by NK cells in FcεRIγ -/mice resulted in better survival. However, it remains unclear whether the FcεRIγ -/-NK cells in this mouse model are comparable to their human counterparts since, in the murine system, adaptive/memory-like NK cells are defined by other features such as Ly49H expression.…”
Section: Discussionsupporting
confidence: 93%
“…FcRγ is often referred to as FcεRIγ since it was first discovered as the third subunit of FcεRI [130]. Later, it was revealed that it is a common subunit of various FcRs and is also able to associate with a number of immune receptors such as blood dendritic cell antigen 2 (BDCA2) and immunoglobulin-like transcript 7 (ILT7) [131].…”
Section: Inhibitory Receptors Of Type I Ifn Productionmentioning
confidence: 99%
“…Murine neutrophils express all FcγR subtypes, of which, FcγRI, FcγRIII, and FcγRIV are activating receptors and FcγRIIB is the sole inhibitory receptor; although levels of FcγRI are reported to be low [23]. In contrast, human neutrophils constitutively express the activating receptors FcγRIIA and FcγRIIIB, in addition to the inhibitory receptor FcγRIIB; expression of FcγRI expression is inducible [23,24]. Furthermore, FcαRI, an activating receptor which binds immunoglobulin A (IgA), is highly expressed on human neutrophils.…”
Section: Murine Vs Human Neutrophilsmentioning
confidence: 99%